2021
DOI: 10.18295/squmj.4.2021.072
|View full text |Cite
|
Sign up to set email alerts
|

Mediastinal hydatidosis with an unusual presentation

Abstract: Hydatidosis is a common zoonotic disease with high prevalence in developing countries. While solitary cyst with unilateral lung involvement is common, bilateral involvement and multiple cysts are rare, seen in 20% and 30% of the cases. Likewise, extensive involvement of extrapulmonary tissues and mediastinum is rare. We report an unusual case of mediastinal hydatidosis mimicking an intrathoracic malignancy in a 24-year-old female. She presented with a history of left-sided chest pain and heaviness in the left … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…To date, one co-infection of Lophomonas with IPA has been reported in one immunocompromised patient [ 17 ] and several IPA cases have co-occurred with pulmonary CE [ 8 ]. It is noted that in some cases of pulmonary hydatidosis, such as mediastinal hydatidosis, a malignancy presentation may be mimicked [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, one co-infection of Lophomonas with IPA has been reported in one immunocompromised patient [ 17 ] and several IPA cases have co-occurred with pulmonary CE [ 8 ]. It is noted that in some cases of pulmonary hydatidosis, such as mediastinal hydatidosis, a malignancy presentation may be mimicked [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical intervention is the treatment of choice for ruptured hydatid cysts, and albendazole 15 mg/kg/day is the recommended drug in the postoperative phase for 3-6 months to prevent a recurrence [5]. The patient in the case study received albendazole for 3 months, and no recurrence was observed on follow-up visits.…”
mentioning
confidence: 99%
“…The liver is the most common site, accounting for 60-70%, while the lungs are the second most common organ involved, with a higher predilection for the right lower lobe [4]. Cysts are usually solitary and unilateral in distribution, while bilateral involvement and multiple cysts are not uncommon, seen in 20% and 30% of cases, respectively [5]. The term complicated cyst includes hydatid cysts with pleural involvement and the associated infection [3].…”
mentioning
confidence: 99%
“…Human is an accidental intermediate host where the organs commonly affected by this disease include the liver (70%) and lungs (20%), while involvement of other organs is rare. However, intra-abdominal hydatidosis can be observed in other organs such as the peritoneum, spleen, kidney, and pancreas [ 7 , 10 , 11 , 13 , 46 ]. In a large-scale abattoir study conducted in Saudi Arabia on 91348 animals (camels 541; cattle 615, goats 48370 and sheep 41822), the prevalence of hydatidosis was 6.86%, 3.63%, 69.6% & 19.85% in camels, cattle, sheep and goats respectively, and liver was the predominant site of infection in all animals [ 42 ].…”
mentioning
confidence: 99%